Value Clarification Technique Integrated with Socioscientific Issues through Role-Playing to Enhance Scientific Literacy in Elementary School - Aisyah, Siti; Kawuryan, Sekar Purbarini (Universitas Muhammadiyah Surakarta, 2024)
This study seeks to examine the differences between the Value Clarification Technique (VCT) model, integrated with socioscientific issues through role-playing, and the more commonly used problem-based learning model in schools. Scientific literacy among elementary school students remains low, necessitating innovative teaching approaches. The research employed a quantitative, quasi-experimental design, specifically utilizing a non-equivalent control group pretest-posttest model. The sample consisted of 71 fifth-grade students, divided into two groups: the experimental group, which received the VCT-based intervention, and the control group, which followed the standard curriculum. Data were collected through pretest and posttest assessments, and hypothesis testing was performed using paired sample t-tests and independent sample t-tests via SPSS 2022. The results indicate that the VCT model, integrated with socioscientific issues through role-playing, significantly improves students' scientific literacy, particularly their ability to explain scientific phenomena. As a critical 21st-century competency, scientific literacy enables students to analyze information, articulate scientific concepts, and draw evidence-based conclusions from data.